Corporate Social Responsibility: A Conceptual Research - Luthfiani, Anin Dyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
In recent years, it can be noticed that academics are still looking at the concept of CSR from a different perspective. This review focuses on the most relevant academic publications and historical events that have influenced the evolution of CSR as a conceptual paradigm. The literature review shows that the future of CSR must also consider recent technological advancements and their role as part of new business frameworks and strategies. The adoption and adaptation of new digitization processes and tools, as well as the incorporation of Artificial Intelligence into the business environment is a relevant challenge not only for the CSR debate, but for companies in general. The main contribution of this article is a structured historical review accompanied by the evolution of CSR and future research opportunities.